2019
DOI: 10.18295/squmj.2019.19.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nitroglycerin versus Lignocaine Spray to Attenuate Haemodynamic Changes in Elective Surgical Patients Undergoing Direct Laryngoscopy and Endotracheal Intubation: A prospective randomised study

Abstract: Objectives: This study aimed to compare the effects of nitroglycerin (NTG) versus lignocaine spray in blunting the pressor response during direct laryngoscopy and endotracheal intubation. Methods: This study was conducted between January and June 2018 in the Department of Anesthesiology, Teerthankar Mahaveer Medical College, Moradabad, India. A total of 90 elective surgical patients of American Society of Anesthesiologists physical status grades I or II were divided into three groups, comprising two treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…However, the fear of the side effects of narcotic drugs always limits the variety of their use. Varshney et al demonstrated the TNG alone was more effective than anesthetic drug in reducing hemodynamic pressor response during intubation (15), which is consistent with the results of our study. Also, the results of the study by Firoozbakhsh et al have found TNG injection to be effective in preventing unwanted complications of intubation (16).…”
Section: Discussionsupporting
confidence: 93%
“…However, the fear of the side effects of narcotic drugs always limits the variety of their use. Varshney et al demonstrated the TNG alone was more effective than anesthetic drug in reducing hemodynamic pressor response during intubation (15), which is consistent with the results of our study. Also, the results of the study by Firoozbakhsh et al have found TNG injection to be effective in preventing unwanted complications of intubation (16).…”
Section: Discussionsupporting
confidence: 93%
“…Tracheal extubation and emergence from anesthesia may cause dangerous increase in myocardial oxygen demand in patients with coronary artery disease or at risk of developing it [18]. During this study, rate pressure product was high in NTG group as compared to Esmolol group, thus NTG should be cautiously used in coronary artery disease patients [19].…”
Section: Wang Et Al In 2003 Studied Effects Of Different Doses Of IV ...mentioning
confidence: 71%
“…In a different investigation, Varshney et al examined the pressor response after the administration of GTN and lignocaine spray during direct laryngoscopy and endotracheal intubation (10) . According to the study, The GTN spray was superior to lignocaine at reducing blood pressure increases during elective laryngoscopy and intubation.…”
Section: Discussionmentioning
confidence: 99%